Validation of PREDICCS using LRO/CRaTER observations during three major solar events in 2012. Issue 6 (6th June 2013) - Joyce, C. J.; Schwadron, N. A.; Wilson, J. K.; Spence, H. E.; Kasper, J. C.; Golightly, M.; Blake, J. B.; Mazur, J.; Townsend, L. W.; Case, A. W.; Semones, E.; Smith, S.; et al.
Abstract: [1] PREDICCS (Predictions of Radiation from Release, EMMREM, and Data Incorporating the CRaTER, COSTEP and other SEP measurements, prediccs.sr.unh.edu) is an online system designed to provide a near real‐time characterization of the radiation environment of the inner heliosphere. PREDICCS utilizes data from various satellites in conjunction with numerical models such as the Earth‐Moon‐Mars Radiation Environment Module (EMMREM) to produce dose rate and particle flux data at the Earth, Moon and Mars. The Cosmic Ray Telescope for the Effects of Radiation (CRaTER) instrument launched aboard the Lunar Reconnaissance Orbiter (LRO) spacecraft in 2009 and designed to measure energetic particle radiation, offers an opportunity to test the capability of PREDICCS to accurately describe the lunar radiation environment. We provide comparisons between dose rates produced by PREDICCS with those measured by CRaTER during three major solar energetic particle (SEP) events that occurred in 2012. In addition, using EMMREM data products together with our archive of measured CRaTER dose rates, we compute the modulation potential at the Moon throughout the LRO mission and, using this, compute the background GCR dose rate during each event. We demonstrate reasonable agreement between PREDICCS and CRaTER dose rates and come to the conclusion that PREDICCS provides credible characterization of the lunar radiation environment. This study represents the first multi‐event validation, via in situ measurement, of radiation models such as EMMREM, which should prove to be valuable in future efforts in risk assessment and in the study of radiation in the inner heliosphere. Key Points: The PREDICCS radiation model is capable of accurate forecasting Dose rates measured by CRaTER and predicted by PREDICCS are in good agreement CRaTER dose rates may be used to compute the modulation potential at the Moon